Pengaruh Kualitas Produk terhadap Keputusan Pembelian dengan Kepercayaan Konsumen sebagai Variabel Mediasi pada Marketplace Shopee di Kalangan Mahasiswa S1 di Daerah Istimewa Yogyakarta - Sumarni, Afrisca Dwi; Indarto, Muhammad Roni (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2026)
This research is conducted with the aim of testing the impact of product quality on purchasing decisions on the Shopee platform, involving consumer trust as a mediating variable. The population targeted by this research is undergraduate students (S1) in the Special Region of Yogyakarta. For sample determination, the researcher applied a non-probability sampling technique using a purposive sampling approach and successfully collected data from 140 respondents. The stages of data evaluation include a series of instrument tests (validity and reliability), prerequisite tests (normality), and hypothesis tests encompassing the F-test and the coefficient of determination (Adjusted R Square). The data processing itself uses the path analysis method assisted by the process macro tool in the IBM SPSS Statistics 26 program. Based on the analysis results, several main points were found, namely: (1) product quality has a positive and significant impact on building consumer trust on Shopee, (2) directly, product quality also has a positive and significant impact on the decision to shop, (3) consumer trust has been proven to have a positive and significant influence on the purchase decision, and (4) product quality has been proven to positively and significantly enhance the purchase decision thru the mediating role of consumer trust.